Comparative Analysis of Oral and Intravenous Rehydration Therapy in Paediatric Acute Gastroenteritis - Imran Yasin, Muhammad Usman Rafique, Rizwan Mahmood, Khurram Nawaz, Husnul Hayat, Sanwal Sardar Nawaz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute gastroenteritis remains one of the leading causes of morbidity and mortality among children worldwide, particularly in developing countries. Objective: To compare the clinical effectiveness, safety, and overall outcomes of oral rehydration therapy and intravenous rehydration therapy in pediatric patients with acute gastroenteritis. Methodology: This comparative cross-sectional study was at Department of Pediatric Medicine, Continental Medical College, Hayat Memorial Hospital Lahore from 1st October 2022 to 31st March 2023. A total of 240 children aged 6 months to 10 years diagnosed with acute gastroenteritis and presenting with mild to moderate dehydration were enrolled. They were equally divided into two groups: Group A received oral rehydration therapy using WHO-formulated reduced-osmolarity oral rehydration solution, and Group B received intravenous rehydration with isotonic fluids. Results: Both therapies achieved 100% rehydration success. The mean time to rehydration was significantly shorter in the IV group (5.8±1.7 hours) than in the oral group (7.4±2.2 hours, p<0.001). However, the oral rehydration group demonstrated a significantly shorter hospital stay (1.6±0.8 days vs. 2.8±1.2 days, p<0.001) and earlier resumption of feeding (p = 0.04). Complications such as vomiting occurred in 15% of the oral group, while IV site phlebitis (6.7%) and mild electrolyte imbalance (7.5%) were noted in the IV group. Conclusion: Both oral and intravenous rehydration therapies are effective for managing dehydration in pediatric acute gastroenteritis. However, oral rehydration therapy offers comparable efficacy with fewer complications, lower costs, and shorter hospitalization, making it the preferred choice for mild to moderate dehydration. Keywords: Dehydration, Patients, Acute gastroenteritis, Diagnosed, Effectiveness